Assessment of air quality index (AQI) in Riyadh, Saudi Arabia. Issue 1 (1st May 2022) - Hassan, R; Rahman, M; Hamdan, A
Abstract: Air pollution is increasingly becoming a main environmental matter in the world. It can impact public health, weather, and climate. Riyadh's air pollution poses significant environmental and health risks. The study aimed to analyze Riyadh's current and future air quality by using AQI. Main six air pollutants are considered, nitrogen dioxide (NO2 ), sulfur dioxide (SO2 ), particulate matter (PM), ground level ozone (O3 ), and carbon dioxide (CO2 ), carbon monoxide (CO). Eleven air quality stations located throughout Riyadh assess the concentration of six standard pollutants daily. A comparison of air quality in Riyadh was done at the local, regional, and international levels. Furthermore, diverse factors such as meteorological seasons, working periods, and the COVID-19 period are taken into account. Industrial emissions, as well as contributions from mobile sources and wind-blown dust, appear to be the principal pollutant sources affecting Riyadh. The measured air quality components for all contaminants were found to be below standard. PM poses the greatest damage to the city's human health of all the pollutants studied. It can be found in practically all locations of air quality stations, even though CO and O3 levels in the city are not at alarming levels.